2012
DOI: 10.1038/ng.2291
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing of liver cancers identifies etiological influences on mutation patterns and recurrent mutations in chromatin regulators

Abstract: Hepatocellular carcinoma (HCC) is the third leading cause of cancer-related death worldwide. We sequenced and analyzed the whole genomes of 27 HCCs, 25 of which were associated with hepatitis B or C virus infections, including two sets of multicentric tumors. Although no common somatic mutations were identified in the multicentric tumor pairs, their whole-genome substitution patterns were similar, suggesting that these tumors developed from independent mutations, although their shared etiological backgrounds m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
722
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 788 publications
(764 citation statements)
references
References 31 publications
38
722
3
1
Order By: Relevance
“…TSC2 mutations were not reported in recent next-generation sequencing studies of HCC (39)(40)(41)(42) and there is only one report finding a TSC1 mutation in HCC (35). The different patient ethnicity (Caucasian HCC) and HCC etiology (HCV þ for Japan HCC) in those studies may account for the differences between those and our results.…”
Section: Discussioncontrasting
confidence: 56%
“…TSC2 mutations were not reported in recent next-generation sequencing studies of HCC (39)(40)(41)(42) and there is only one report finding a TSC1 mutation in HCC (35). The different patient ethnicity (Caucasian HCC) and HCC etiology (HCV þ for Japan HCC) in those studies may account for the differences between those and our results.…”
Section: Discussioncontrasting
confidence: 56%
“…Whole-genome sequencing of HCCs has identified recurrent mutations in chromatin regulators that can directly influence chromatin's structure and activity. (24). Chromatin regulators exert posttranslational modifications of histone proteins by altering their methylation, ubiquitinylation, and acetylation status and have a direct influence on gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have revealed etiological patterns and multiple genes/pathways signifying initiation and progression of HCC. These pathways include CTNNB1/WNT‐β‐catenin, TPp53, ARID1/2s, HGF/c‐Met, and vascular endothelial growth factor/angiogenic signaling 5, 6, 7, 8, 9, 10, 11, 12. However, unlike the transforming growth factor β (TGF‐β) pathway, loss of p53 and/or activation of β‐catenin do not spontaneously drive HCC in animal models 13, 14, 15…”
Section: Introductionmentioning
confidence: 99%